Molecular characterisation of the interactions between staphylococcus aureus and elastin - Downer, Robert G. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Microbiology, 2002)
Previous studies have shown that a cell-surface 83 kDa elastin-binding protein of Staphylococcus aureus (EbpS) mediates binding to soluble elastin. Antibodies were produced to the N terminus and C terminus of EbpS. Western immunoblotting identified EbpS as an 83 kDa protein in whole cell lysates of S. aureus. Release of EbpS from purified S. aureus cell envelopes, with either lithium chloride or sodium dodecyl sulphate, revealed that the protein is associated with the cell surface by a different mechanism to that of the typical cell-wall-associated protein ClfA, which belongs to a family of staphylococcal extracellular matrix-binding proteins that are covalently anchored to the cell wall and are known as microbial surface components recognising adhesive matrix molecules (MSCRAMMs). EbpS was localized to the cytoplasmic membrane of S. aureus and Lactococcus lactis expressing EbpS by cellular fractionation using the stabilised protoplast method whereby cell-wall-associated proteins were released from the cell surface by enzymatic digestion of the cell wall peptidoglycan while maintaining an osmotically stable protoplast. In addition, EbpS was detected in the purified membrane fraction of S. aureus that had been prepared by mechanically smashing the cells and separating fractions by differential centrifugation.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin